2020
DOI: 10.1080/23311886.2020.1818373
|View full text |Cite
|
Sign up to set email alerts
|

Paddy, rice and food security in Malaysia: A review of climate change impacts

Abstract: Malaysia has focused its self-sufficiency policy on rice and paddy production, which are the country's primary staple food and food crop. Throughout the Eleventh Malaysian Plan (2016)(2017)(2018)(2019)(2020) and National Agro-Food Policy (2011-2020, Malaysia continues its proactive and progressive measures to promote paddy and rice sector development. The impacts of climate change, however, are projected to exacerbate challenges in increasing paddy yields and achieving food security in the future. Hence, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…With an ever-increasing human population, it is challenging to ensure food security for the general population. To counter the demand, rice production needs to be increased to fulfill this need [ 1 ]. However, throughout the growing season, reduction in rice yields has been detected and are caused by a variety of phytopathogens including bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…With an ever-increasing human population, it is challenging to ensure food security for the general population. To counter the demand, rice production needs to be increased to fulfill this need [ 1 ]. However, throughout the growing season, reduction in rice yields has been detected and are caused by a variety of phytopathogens including bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Projections suggest that global mean temperature increases will have adverse impacts such as increased heatwaves, agricultural droughts, floods, and reduced crop yields [3]. A recent study by Firdaus et al [4] indicated that minimum and maximum In general, three main approaches have been widely used to analyze the impacts of climate change on agriculture-one of which is panel data analysis [22]. In panel data analysis, omitted variables can be overcome by including regional dummies in the model.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that climate variables have a significant impact on agriculture yield [30]. Climate parameters such as increased temperature, high or low precipitation as well as extreme weather events adversely affect crop productions, thus challenging food security [4]. Studies projected that increased atmospheric CO 2 concentration would have a mixture of positive and negative effects on rice production, consumption, distribution as well as national development [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On an average, Malaysians consumed 80 kg of rice per person per year, which is about 26% of the total caloric intake per day. Compared to the global rice production, Malaysia's total rice production area is only about 0.7 million ha, contributing a mere 0.4% of the total global output, which is the lowest in South East Asia (Firdaus et al, 2020). As per the latest available figure, over 2.7m MT of rice was consumed in Malaysia, wherein 67-70% is produced locally, and the remaining 33-30% is imported primarily from Thailand, Vietnam and Pakistan.…”
Section: Introductionmentioning
confidence: 99%